EVALUASI NORMA KEDAULATAN RAKYAT DALAM KONSTITUSI DAN PELAKSANAANNYA DALAM KERANGKA NEGARA HUKUM DEMOKRATIS - Endang Puji Lestari; Muh Risnain (Indonesian Journal of Law and Policy Studies, 2020)
The issue of determining the winners of the presidential election, the tenure of president and vice president, the principle of electing the regional head and the legal regime of the regional head are issues that are still not completely regulated in the constitution and need improvement. Several articles in the constitution relating to people's sovereignty should the MPR make changes to article 6 paragraph (3), article 7, article 18 paragraph (4) and article 23 paragraph (2) by looking at the practice of state administration and the dynamic development of democratic life. MPR as an institution that has the authority to change the constitution can carry out the process of changing the constitution according to the mechanism of article 37 of the 1945 Constitution. such as the absence of the presidential treshold regime and separate elections between legislative elections, presidential elections, local elections. Therefore, the Parliament and the President are called upon to amend Law No. 7 of 2017 concerning elections in line with constitutional values